2019
DOI: 10.3892/etm.2019.7146
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of miR‑421 on humeral fracture and heterotopic ossification in elderly patients

Abstract: The present study aimed to investigate the role of miR-421 and bone morphogenetic protein-2 (BMP-2) in the bone tissues and blood of elderly patients with humeral fractures and heterotopic ossification. A total of 38 patients with humeral fractures, including 16 patients who received surgery within 1-7 days of fracture and 22 patients who received surgery within 8-14 days of fracture, were enrolled. An additional 18 patients who had heterotopic ossification and 26 patients who had humeral fracture and not hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…BMP signaling is transduced via p38 mitogen-activated protein kinase (MAPK) [ 39 ] and/or SMAD complexes [ 40 ]. The canonical Wnt /ß-catenin pathway is also implicated in chondrocyte maturation and osteoblast differentiation [ 41 , 42 ]. A recent study showed that TNF inhibited BMP2-mediated osteogenesis via a strong activation of p38 MAPK in C2C12 and MC3T3-E1 cells whilst inhibition of p38 rescued the expression of RUNX2 and other osteogenic markers induced by BMP2 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMP signaling is transduced via p38 mitogen-activated protein kinase (MAPK) [ 39 ] and/or SMAD complexes [ 40 ]. The canonical Wnt /ß-catenin pathway is also implicated in chondrocyte maturation and osteoblast differentiation [ 41 , 42 ]. A recent study showed that TNF inhibited BMP2-mediated osteogenesis via a strong activation of p38 MAPK in C2C12 and MC3T3-E1 cells whilst inhibition of p38 rescued the expression of RUNX2 and other osteogenic markers induced by BMP2 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These pathways should not be viewed as independent, as crosstalk between them occurs [117][118][119][120]. BMP2 is overexpressed in clinically evolving HO tissue after trauma [121,122]. Augmented BMP signalling also occurs following trauma-induced HO development in animal models whilst BMP antagonism reduces HO severity [123,124].…”
Section: Bmp15mentioning
confidence: 99%
“…However, patients with HO show significantly lower expression of miR421 in their bone and blood, compared to patients who did not develop HO. Thus, miR421 could play a regulatory role in the HO induction [ 180 ]. It was documented that BMP2, i.e., the strongest osteogenic induction factor, was the direct target of miR421.…”
Section: The Role Of Mirna and Lncrna In Heterotopic Ossificationmentioning
confidence: 99%
“…Verification of the role of BMP2 in patients with HO induced by humeral fracture showed a significantly increased expression of BMP2 in ossified tissues and blood. Therefore, the development of HO may be related to the up-regulation of BMP2 and down-regulation of miR421 [ 180 ].…”
Section: The Role Of Mirna and Lncrna In Heterotopic Ossificationmentioning
confidence: 99%